Cannabinoid Receptor 2-Centric Molecular Feedback Loop Drives Necroptosis in Diabetic Heart Injuries. Issue 2 (30th November 2022) - Gao, Pan; Cao, Mengying; Jiang, Xueli; Wang, Xiaolin; Zhang, Guoping; Tang, Xinru; Yang, Chunjie; Komuro, Issei; Ge, Junbo; Li, Liliang; Zou, Yunzeng
Abstract : Background: Diabetic heart dysfunction is a common complication of diabetes. Cell death is a core event that leads to diabetic heart dysfunction. However, the time sequence of cell death pathways and the precise time to intervene of particular cell death type remain largely unknown in the diabetic heart. This study aims to identify the particular cell death type that is responsible for diabetic heart dysfunction and to propose a promising therapeutic strategy by intervening in the cell death pathway. Methods: Type 2 diabetes models were established using db/db leptin receptor–deficient mice and high-fat diet/streptozotocin–induced mice. The type 1 diabetes model was established in streptozotocin-induced mice. Apoptosis and programmed cell necrosis (necroptosis) were detected in diabetic mouse hearts at different ages. G protein–coupled receptor–targeted drug library was searched to identify potential receptors regulating the key cell death pathway. Pharmacological and genetic approaches that modulate the expression of targets were used. Stable cell lines and a homemade phosphorylation antibody were prepared to conduct mechanistic studies. Results: Necroptosis was activated after apoptosis at later stages of diabetes and was functionally responsible for cardiac dysfunction. Cannabinoid receptor 2 (CB2R) was a key regulator of necroptosis. Mechanically, during normal glucose levels, CB2R inhibited S6 kinase–mediated phosphorylation of BACH2 at serine 520, thereby leading to BACH2 translocation to the nucleus, where BACH2 transcriptionally repressed the necroptosis genes Rip1, Rip3, and Mlkl . Under hyperglycemic conditions, high glucose induced CB2R internalization in a β-arrestin 2–dependent manner; thereafter, MLKL (mixed lineage kinase domain-like), but not receptor-interacting protein kinase 1 or 3, phosphorylated CB2R at serine 352 and promoted CB2R degradation by ubiquitin modification. Cardiac re-expression of CB2R rescued diabetes-induced cardiomyocyte necroptosis and heart dysfunction, whereas cardiac knockout of Bach2 diminished CB2R-mediated beneficial effects. In human diabetic hearts, both CB2R and BACH2 were negatively associated with diabetes-induced myocardial injuries. Conclusions: CB2R transcriptionally repressed necroptosis through interaction with BACH2; in turn, MLKL formed a negative feedback to phosphorylate CB2R. Our study provides the integrative view of a novel molecular mechanism loop for regulation of necroptosis centered by CB2R, which represents a promising alternative strategy for controlling diabetic heart dysfunction.